Establishment of organotypic epithelial raft cultures as a model of high-grade cervical intraepithelial neoplasia and quantification of treatment effects through machine learning-based cell counting [data] - Köhler, Richard M.; Stark, Hans-Jürgen; Martin, Iris; Altmann, Joel; Kalteis, Martin Simon; Knebel Doeberitz, Magnus von; Prigge, Elena-Sophie (Universität, 2024)
This dataset contains the raw data and code used for analyses in the doctoral dissertation "Establishment of organotypic epithelial raft cultures as a model of high-grade cervical intraepithelial neoplasia and quantification of treatment effects through machine learning-based cell counting". The data is comprised of annotations and cell detections in HE-stained sections from 3D organotypic raft cultures, as well as generated statistics and plots that are depicted in the results section of the corresponding doctoral dissertation. For instructions on how to navigate the dataset, run code and reproduce the results, please refer to the README file.